Optimizing copper catalytic converter designs for emission reduction in automatic motorcycles using grey relational analysis - Sudirman Rizki Ariyanto; Warju Warju; Komarudin Komarudin; Ata Syifa' Nugraha; Susi Tri Umaroh (Politeknik Negeri Lhokseumawe, 2025)
Vehicle emissions remain a major environmental challenge in urban areas, particularly in developing countries like Indonesia, where motorcycles dominate transportation. Automatic motorcycles pose specific emission control difficulties due to their engine characteristics. This study experimentally evaluates six copper-metallic catalytic converter designs installed on a 150cc automatic motorcycle under idle and 3000 rpm conditions. Exhaust emissions of carbon monoxide (CO) and hydrocarbons (HC) were measured using a gas analyzer. Grey Relational Analysis (GRA) was employed to optimize the design parameters. The E3 design (curvature height: 4 mm, diameter: 54 mm, length: 100 mm) exhibited the best performance, reducing CO to 3.72% and HC to 539 ppm. Compared to standard designs, E3 improved emission reduction by 18–36%. These findings confirm that catalyst geometry significantly influences emission control and demonstrate the effectiveness of GRA in multi-parameter optimization. The results contribute to the development of efficient, affordable catalytic converters, supporting sustainable transportation and aligning with SDG 13 goals for climate action.